Mid‐life epigenetic age, neuroimaging brain age, and cognitive decline: Coronary Artery Risk Development in Young Adults (CARDIA) Study. (31st December 2021) - Zheng, Yinan; Habes, Mohamad; Gonzales, Mitzi M.; Pomponio, Raymond; Nasrallah, Ilya M.; Davatzikos, Christos; Seshadri, Sudha; Launer, Lenore J.; Sorond, Farzaneh; Sedaghat, Sanaz; Bryan, Nick; Sidney, Stephen; et al.
Abstract: Background: Establishing biological aging markers that predict cognitive performance may aid early identification of individuals at risk for accelerated cognitive decline and promote the development of interventions to preserve optimal cognitive function across the lifespan. We investigated two distinct classes of biological aging markers, 1) epigenetic aging, an emerging class of blood‐derived DNA methylation markers that aggregate aging‐related DNA methylation information; and 2) Spatial Patterns of Abnormality for Recognition of Brain Aging (SPARE‐BA), a composite magnetic resonance imaging (MRI) index of brain aging. Method: We evaluated the cross‐sectional and prospective associations between both classes of aging markers and cognitive performance across a 15‐year follow‐up in the biracial CARDIA cohort of approximately 1, 000 middle‐aged adults, using multiple linear regression and logistic regression. We compared the diagnostic performance of both aging markers using receiver operating characteristic (ROC) curve analysis. Result: We found that accelerated epigenetic aging and brain aging were both cross‐sectionally and prospectively associated with worse cognitive outcomes. Specifically, every 5‐year faster epigenetic/brain aging is on average associated with 9.7% standard deviation (SD) higher in Stroop Test score, 7.7% SD lower in Rey Auditory Verbal Learning Test score, and 10.3% SD lower in Digital Symbol Substitution Test (all false‐discovery‐rate‐adjusted p <0.05). ROC analysis showed that a combined model with both epigenetic aging and brain aging markers optimized discriminability of individuals with lower cognitive performance 5 to 10 years later (area under the ROC curve: 0.70; 95% confident interval: 0.63‐0.77, Figure). Epigenetic and brain aging markers were weakly correlated with one another (Person's r =0.17) and not statistically significant. Conclusion: Our results showcase the significance of novel biological aging markers for cognitive health. Accelerated epigenetic aging and brain aging may capture distinct facets of biological aging and may jointly serve as early indicators of future cognitive decline and inform early interventions to prevent or delay cognitive impairment.